Instrument Tests on the Selection of New Admission - Milkha, Milkha; Simega, Berthin; Mangera, Elisabet (Indonesian Journal of Educational Studies, 2014)
This study aims to describe the validity, reliability, level of difficulty, and distinguishing test instruments Indonesian field of study, and to describe the factors causing low test scores Indonesian field of study. Data sourced from Toraja STKAN student admission. Data were collected by using questionnaires, interviews, observation, and documentation. Quantitatively, the data were analyzed with Pearson product moment, then continued by describing the findings. The research found that: 1) the instrument test subjects classified Indonesian valid and reliable; 2) different power index was found to vary, while the level of difficulty of items is not balanced; 3) the cause of the low value of the test field of study Indonesian language, which is a factor that is not a matter script maker to test instruments and factors mean prospective students who do guessing the answer.